Transformation from student to occupational therapist: Using the Delphi technique to identify the threshold concepts of occupational therapy. (29th December 2015) - Nicola‐Richmond, Kelli M.; Pépin, Geneviève; Larkin, Helen
Abstract : Background/aim: Understanding and facilitating the transformation from occupational therapy student to practitioner is central to the development of competent and work‐ready graduates. However, the pivotal concepts and capabilities that need to be taught and learnt in occupational therapy are not necessarily explicit. The threshold concepts theory of teaching and learning proposes that every discipline has a set of transformational concepts that students must acquire in order to progress. As students acquire the threshold concepts, they develop a transformed way of understanding content related to their course of study which contributes to their developing expertise. The aim of this study was to identify the threshold concepts of occupational therapy. Method: The Delphi technique, a data collection method that aims to demonstrate consensus in relation to important questions, was used with three groups comprising final year occupational therapy students ( n  = 11), occupational therapy clinicians ( n  = 21) and academics teaching occupational therapy ( n  = 10) in Victoria, Australia. Results: Participants reached consensus regarding 10 threshold concepts for the occupational therapy discipline. These are: understanding and applying the models and theories of occupational therapy; occupation; evidence‐based practice; clinical reasoning; discipline specific skills and knowledge; practising in context; a client‐centred approach; the occupational therapist role; reflective practice and; a holistic approach. Conclusion: The threshold concepts identified provide valuable information for the discipline. They can potentially inform the development of competencies for occupational therapy and provide guidance for teaching and learning activities to facilitate the transformation to competent practitioner.